Multistate methodology improves risk assessment under time‐varying drug intake—a new view on pregnancy outcomes following coumarin exposure. Issue 5 (3rd March 2019) - Bluhmki, Tobias; Fietz, Anne‐Katrin; Stegherr, Regina; Beck, Evelin; Padberg, Stephanie; Beyersmann, Jan; Schaefer, Christof; Meister, Reinhard
Abstract: Purpose: Observational cohort studies are essential to evaluate the risk of adverse pregnancy outcomes associated with drug intake. Besides left truncation and competing events, it is crucial to account for the time‐dynamic pattern of drug exposure. In fact, potentially harmful medications are often discontinued, which might affect the outcome. Ignoring these challenges may lead to biased estimation of drug‐related risks highlighting the need for adequate statistical techniques. Methods: We reanalyze updated data of a recently published study provided by the German Embryotox pharmacovigilance institute. The aim of the study was to quantify the effect of discontinuation of vitamin K antagonist phenprocoumon on the risk of spontaneous abortion. Results: We outline multistate methodology as a powerful method removing bias in probability estimation inherent to commonly used crude proportions. We incorporate time‐dependent discontinuation and competing pregnancy outcomes as separate states in a multistate model, which enables the formulation of hazard‐based Cox proportional hazard models and the application of so‐called landmark techniques. Results show that early discontinuation of phenprocoumon substantially reduces the risk of spontaneous abortion, which is of great importance for both pregnant women and treating physicians. Conclusions: An adequate handling of discontinuation times is essential when analyzing the risk of spontaneous abortion. The proposed concepts are not restricted to pregnancy outcome studies but have broad usage in other fields of epidemiology. Our nontechnical report may provide guidance for the design and analysis of future studies. Example code is provided.